A new non-complex synthesis of NiO nanofoams for hydrogen storage applications. Issue 2 (21st December 2022) - Thill, Alisson S.; Lima, Dirléia S.; Perez-Lopez, Oscar W.; Manfro, Robinson L.; Souza, Mariana M. V. M.; Baptista, Daniel L.; Archanjo, Bráulio S.; Poletto, Fernanda; Bernardi, Fabiano
Abstract : NiO nanofoams show improved results for hydrogen storage applications. Abstract : The use of nanofoams is beneficial for a wide range of applications ranging from catalysis to plasmonics. The present communication reports on the non-complex synthesis of NiO nanofoams and their use for hydrogen storage applications. The results point to an improved hydrogen storage capacity at room temperature and ambient pressure of hydrogen as compared to Ni-based systems in the literature. DFT calculations point to a quasi-molecular bonding of the H2 molecule at the surface of the NiO nanofoams. The results open new possibilities for the design of future smart materials for hydrogen storage applications and other fields.